ETHNOMATHEMATICS SASAK: EKSPLORASI GEOMETRI TENUN SUKU SASAK SUKARARA DAN IMPLIKASINYA UNTUK PEMBELAJARAN - Sabilirrosyad Sabilirrosyad (Jurnal Tatsqif, 2016)
The current research aims to explore the examples of mathematical ideas which exist in motives produced by weavers in Sukarara. Although, it is still in the form of the dialogue and preliminary observations, revealed the principles of geometry such as translation, reflection, rotation and enlargement. These principles are often used in the patterns in making songket motifs in Sukarara village, Central Lombok. Weaving by most of the mothers of the households in this Sukarara indirectly applying the principles of geometry, even if they are not yet familiar with geometric concepts taught in school, but they can apply them in the form of beautiful and high-value motifs. It is important for us to learn and teach the students to be used as sources in contextual learning.